The fundamental motor skills and motor coordination performance of children in West Sumatera Province, Indonesia - Oktarifaldi; Soni Nopembri; Yudanto; Mohd Izwan bin Shahril (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aims. Good motor coordination is needed to achieve good fundamental motor skills. This study aimed to analyze and describe the relationship between fundamental motor skills and motor coordination performance of elementary school students aged 7 to 9 years old.